2019
DOI: 10.1136/heartjnl-2019-315397
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of atrial fibrillation in northeast China: a cross-sectional study, 2017–2019

Abstract: ObjectiveTo evaluate the epidemiology of atrial fibrillation (AF) in northeast China.MethodsThis cross-sectional survey using a multistage, stratified and cluster random sampling method was conducted in Liaoning Province between September 2017 and March 2019. A total of 18 796 participants (28.9% urban, 71.1% rural) aged ≥40 years were included. All participants completed a questionnaire and underwent a physical examination and ECG. AF was diagnosed according to history and ECG findings.ResultsThe overall AF p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 29 publications
5
29
3
Order By: Relevance
“…7 Previous studies have consistently con rmed that the management of hypertension could signi cantly reduce the likelihood of stroke recurrence and long-term adverse outcomes in patients with a history of ischemic stroke. 8 In our previous study, we found that hypertension was prevalent in rural northeast China's stroke population; 6 however, detailed information regarding this remains unclear. In the present study, we conducted a cross-sectional survey to pro le the current hypertensive status of the ischemic stroke population for future research on secondary prevention strategies in northeast China.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…7 Previous studies have consistently con rmed that the management of hypertension could signi cantly reduce the likelihood of stroke recurrence and long-term adverse outcomes in patients with a history of ischemic stroke. 8 In our previous study, we found that hypertension was prevalent in rural northeast China's stroke population; 6 however, detailed information regarding this remains unclear. In the present study, we conducted a cross-sectional survey to pro le the current hypertensive status of the ischemic stroke population for future research on secondary prevention strategies in northeast China.…”
Section: Introductionmentioning
confidence: 94%
“…Written informed consent was obtained from all participants. 6,10 The prevalence time was determined as August 31, 2017, while new onset stroke cases during the survey were excluded in the calculation of stroke prevalence. Participants with a doubtful or certain history of stroke were further con rmed by well-trained neurologists in accordance with the World Health Organization recommendations.…”
Section: Study Population and Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Atrial fibrillation (AF) is one of the most common arrhythmias seen in clinical practice. An epidemiological study reports the total incidence of AF in China to be 1.1% [1]. As the proportion of older persons in a population continues to increase, so does the incidence of atrial fibrillation.…”
Section: Introductionmentioning
confidence: 99%